2021
DOI: 10.13189/ujm.2021.090202
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of External Environment on Competitive Advantage through SME Differentiation Strategy in Central Java

Abstract: The competitiveness of Small and Medium Enterprises (SMEs) in Indonesia is still very low and vulnerable compared to increasingly uncertain business environment dynamics. Changing conditions require SMEs carry out continuous and systematic analysis of the external environment, so that owners who carry out strategic planning get information through various sources in the external environment. This is done to maintain a competitive advantage and as an effort to realize unexpected opportunities and progress. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…By analyzing the constituent elements of cross-border e-commerce trade and industrial clusters, and combining the continuous interactive effect between the two, scholars have found that there is a sustainable synergistic development relationship between the crossborder e-commerce trade and industrial clusters [49]. Based on the research literature of relevant scholars [50], cross-border e-commerce trade theory, industrial economics theory, sustainable development theory, etc., this paper summarizes the inherent law of the coordinated development of cross-border e-commerce trade and industrial clusters.…”
Section: Analysis Of the Mechanism Of Collaborative Developmentmentioning
confidence: 99%
“…By analyzing the constituent elements of cross-border e-commerce trade and industrial clusters, and combining the continuous interactive effect between the two, scholars have found that there is a sustainable synergistic development relationship between the crossborder e-commerce trade and industrial clusters [49]. Based on the research literature of relevant scholars [50], cross-border e-commerce trade theory, industrial economics theory, sustainable development theory, etc., this paper summarizes the inherent law of the coordinated development of cross-border e-commerce trade and industrial clusters.…”
Section: Analysis Of the Mechanism Of Collaborative Developmentmentioning
confidence: 99%
“…According to Fu et al (2021) the external environment, which includes economic, social, political, technological, and natural environmental factors, can affect business performance. These factors can provide challenges and opportunities for companies in achieving organizational goals (Jaya et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Globalization has demanded business organizations to be able to adapt quickly to environmental changes. In order to achieve competitive advantage, it is necessary to analyse the competitive environment, choose a strategy, and have adequate resources [28]. In such circumstances, the company's policies, strategies and operations will not be solely shareholder-centered, but will take into account other stakeholders (e.g., governments, political groups, unions, communities, employees, suppliers and customers) and members of the public as a whole [3].…”
Section: Review Of the Theory Underlying Researchmentioning
confidence: 99%